2020
DOI: 10.1186/s12903-020-1018-8
|View full text |Cite
|
Sign up to set email alerts
|

What factors contribute to the self-reported oral health status of Arab adolescents? An assessment using a validated Arabic-WHO tool for child oral health (A-OHAT)

Abstract: Background: The current study was performed; to validate the Arabic version of WHO child oral health assessment tool (A-OHAT), to assess the oral health status of Arab school children and finally to identify the important risk factors associated with the poor teeth and gum conditions of school children. Methods: A cross-sectional study with two-staged simple random sampling technique was implemented. A-OHAT, a self-assessment tool was subjected to psychometric analyses with the respondents being high school ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…In a study that sampled 520 boys and 333 girls from the Jazan region, nearly 91% of them had at least one decayed tooth in their oral cavity [ 16 ]. These results were consistent with another recent study that utilized self-perceived measure to assess the teeth condition of school-going children [ 17 ]. However, the OHRQoL construct and subsequently the Family Impact Scale has not been administered in this region, thus portraying the dearth of imperative evidence.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a study that sampled 520 boys and 333 girls from the Jazan region, nearly 91% of them had at least one decayed tooth in their oral cavity [ 16 ]. These results were consistent with another recent study that utilized self-perceived measure to assess the teeth condition of school-going children [ 17 ]. However, the OHRQoL construct and subsequently the Family Impact Scale has not been administered in this region, thus portraying the dearth of imperative evidence.…”
Section: Introductionsupporting
confidence: 93%
“…Thus, the link to the questionnaire was emailed or sent through the WhatsApp messaging service. Nevertheless, parent’s perception to determine oral health status of children has been used earlier and found to somewhat represent the clinically examined oral health status [ 17 , 24 , 25 ]. Findings show that, because of the poor oral health condition of children, the parents reported the need to take time off from work, impaired sleep and regular activities, and financial distress, and this result was similar to the response received from parents residing in a more developed country with higher Gross Domestic Product (GDP) and a better healthcare infrastructure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Known risk factors for caries are poor oral health perception [ 25 ] and poor oral health behaviors such as low frequency of tooth-brushing [ 26 ], non-use of fluoridated toothpaste [ 27 ], poor dental service utilization [ 25 ], high frequency of consumption of refined carbohydrates [ 28 ], and cigarette smoking [ 29 , 30 ]. Sociodemographic variables such as sex (females are more at risk for caries than males) [ 31 , 32 ] and age (the risk for caries increases with age) [ 33 ]; and familial factors such as low socioeconomic status [ 34 ], birth rank (last primogenitors) [ 35 ], large family size [ 35 ] and parental living status (absence of one or both parents) [ 36 ] can also be risk factors for caries.…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out in the capital city of Saudi Arabia showed that about 83% of children have at least one untreated carious tooth [ 6 ]. Furthermore, the prevalence of tooth decay and gum diseases was nearly the same in children of the less developed province of Jazan [ 8 ]. Thus, it is plausible that there is underutilization of free oral health services in Saudi Arabia, leading to increased oral health problems in children, and dental fear could be one of the important factors.…”
Section: Introductionmentioning
confidence: 99%